Temporal variability of nocturnal turbulent fluxes determined from two different methodologies at the level of 325 m above the Amazon rainforest - Santos, Diego Jatobá (2020)
The present study aimed to analyze and compare the temporal variability of the nocturnal fluxes of CO2, sensitive and latent heat, calculated from two different methodologies: one with a 5-minute temporal window (using the eddy covariance technique), and another with 109 minutes (from multiresolution decomposition). For this, night series of 25 nights were used between October and November 2015. The analyzes were made for two groups of distinct turbulence patterns: one with intermittent regime and the other with homogeneous turbulence. The results showed that the fluxes obtained by the classical method of eddy covariance were dependent on the intensity of the turbulence. On the other hand, the fluxes calculated from the multiresolution decomposition technique showed significant fluctuations in the temporal evolution of all scalars analyzed, with the largest percentage differences between the two approaches occurring in the homogeneous turbulence regime group, which was characterized by predominantly weak turbulent activity throughout the night. In the comparison made, the methodology employed in the 109-minute window showed greater efficiency in the estimates of exchanges at 325 m in the ATTO tower, especially during conditions of low turbulent activity.